2305. Staphylococcus aureus Screening and Decolonization for Pediatric Patients Undergoing Cardiovascular Surgery at Texas Children's Hospital (TCH): A Trainee Quality Improvement Initiative. (26th November 2018) - Foster, Catherine; Ruderfer, Daniel; Lamb, Gabriella; Boguniewicz, Juri; Rochat, Ryan; Marquez, Lucila; Palazzi, Debra; Bocchini, Claire E
Abstract: Background: Colonization with Staphylococcus aureus increases the risk of developing healthcare-associated infections (HAIs) in adults, but its role in pediatrics remains unclear. We hypothesized that use of a S. aureus screening and decolonization protocol for pediatric patients undergoing cardiovascular (CV) surgery would result in a reduction of invasive S. aureus infections. Methods: A S. aureus screening and decolonization protocol (Table 1) was implemented for patients undergoing CV surgery at TCH on January 1, 2018. We retrospectively identified and reviewed charts of pediatric patients with S. aureus infections following CV surgery pre-protocol (2017) and post-protocol (January 1, 2018–March 31, 2018). We defined invasive S. aureus infections as: bacteremia, mediastinitis, superficial and deep surgical site infections (SSIs) and ventilator-associated pneumonias (VAPs). A subset of charts were reviewed pre- and post-protocol for methicillin-resistant S. aureus (MRSA) polymerase chain reaction (PCR) result, use of mupirocin and chlorhexidine gluconate (CHG), and choice of intraoperative antibiotic. Data were analyzed with Fisher's exact. Results: Of 694 pediatric CV surgery patients in 2017, we identified 13 patients with 15 invasive S. aureus infections: bacteremia (5), VAP (4), and SSI (6). Twelve of these infections were caused by methicillin-susceptible S. aureus (MSSA) and 3 were MRSA. The median time to infection was 19 days. In the first 3 month post-protocol period, there were 175 pediatric CV surgery patients with 0 invasive S. aureus infections. Seventy-five charts each were reviewed pre- and post-protocol to assess protocol adherence (Figure 1). Post-protocol MRSA screening peaked at 64%, which increased further to 70% when excluding infants <30 days. Of 40 patients screened with a MRSA PCR, only 1 (2.5%) was positive. Cefazolin use remained high pre- and post-protocol (72/75 vs. 73/75 respectively). Conclusion: Most pediatric invasive S. aureus infections are caused by MSSA. Following protocol implementation, we observed a decrease in invasive S. aureus infections in CV surgery patients at TCH ( P = 0.05), though continued monitoring for protocol compliance and development of S. aureus and other bacterial infections are needed. Disclosures: All authors: No reported disclosures.